Stundets’ Generalization on Functional Thinking: A Study of Three-Dimensional Cognitive Style: A STUDY OF THREE-DIMENSIONAL COGNITIVE STYLE - Khikmiyah, Fatimatul; Siswono, Tatag Yuli Eko; Lukito, Agung (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
This study is a descriptive qualitative study that aims to explore junior high school students’ generalization on functional thinking viewed from students’ differences on cognitive style, verbalizer, spatial visualizer and object visualizer. The subjects of this study were three male students, ages 14-15 years old, on East Java Indonesia. The Object-Spatial Imagery and Verbal Questionnaire (OSIVQ) were used to get the data of students’ cognitive style. This study used in-depth interviews using a pattern task and an interview guide. Time triangulation used for internal validity. The process of analyzing the data consists of data condensation, presentation of data and drawing conclusions. This study found that students with cognitive styles differences have different strategies in making generalization on functional thinking. The strategies used are counting from a drawing, whole-object strategies, and functional strategies. This study further examined how these three students came up with the strategies and what the mathematics expression used of  configuration. The results of this research show the importance of identifying students' cognitive styles before studying mathematics so that teachers can provide appropriate treatment and scaffolding so that students can achieve their learning goals optimally.